Prognostic implication of serum vascular endothelial growth factor in advanced hepatocellular carcinoma staging - (:unkn) unknown (ELSEVIER ESPANA, 2013)
Background. Staging systems have considerable impact on hepatocellular carcinoma (HCC) treatment approaches and outcomes. There is an unmet need to improve their stratification ability. We have evaluated four commonly used staging systems and assessed whether angiogenic biomarker vascular endothelial growth factor (VEGF) could improve their prognostic stratification. Material and methods. Four staging systems; Okuda, Cancer of the Liver Italian Program (CLIP), Barcelona Clinic Liver Cancer (BCLC), and Child-Pugh were evaluated in 78 HCC patients; their stratification abilities were detected by Kaplan-Meier curves and log-rank test; their accuracies of predicting survival were compared with the concordance index. Serum VEGF levels were measured using ELISA method. Recursive partitioning was used to determine the optimal VEGF cutoff. The prognostic significance of VEGF cutoff and other parameters were analyzed using univariate and multivariate models. Results. None of the staging systems demonstrated better discriminatory ability in predicting survival. The four staging systems did not reveal significant differences in probability of survival across their intermediate-advanced stages. Optimal cutoff identified for VEGF was 445 pg/mL. In advanced HCC, VEGF level (p = 0.004) and in early HCC, bilirubin level (p = 0.009) were identified as the independent prognostic factors. Survival comparison with high and low VEGF levels was significant for advanced HCC, while insignificant for early disease. Conclusion. Staging systems with conventional parameters did not provide good prognostic stratification for survival in advanced HCC population. Serum VEGF level was an independent predictor of survival in advanced HCC, and provided more survival homogeneity within the advanced stages of conventional staging systems.
Keywords: Biomarker; Stratification; Survival; Tumor angiogenic activity; Intrinsic tumor feature; RADIOFREQUENCY ABLATION; SYSTEMS; EXPRESSION; SURVIVAL; CLIP; PREDICT; OKUDA; CHEMOEMBOLIZATION; PROGRESSION; MORTALITY